2019
DOI: 10.1182/blood-2019-128849
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Time to Emergency Hip Surgery in Patients Taking Oral Anticoagulants

Abstract: Introduction Surgical intervention within 48 hours of admission in patients with acute hip fractures has been associated to lower morbidity and mortality. Patients anticoagulated with Vitamin K Antagonists (VKAs) have longer time to corrective surgery than those not anticoagulated. Sparse data exists on time to surgery (TTS) in patients taking direct oral anticoagulants (DOACs). The aim of this study is to establish TTS among non-anticoagulated and anticoagulated patients taking either VKA or DO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…First, none of the included studies accounted for the competing risk of death with each endpoint. This is relevant given the association between time to surgery, pre‐injury anticoagulation status, and mortality 8,33 . Nonetheless, there was consistency in directionality between different endpoints in our study, whereby increased estimated blood loss among anticoagulated patients led to the same group requiring higher transfusion utilization.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…First, none of the included studies accounted for the competing risk of death with each endpoint. This is relevant given the association between time to surgery, pre‐injury anticoagulation status, and mortality 8,33 . Nonetheless, there was consistency in directionality between different endpoints in our study, whereby increased estimated blood loss among anticoagulated patients led to the same group requiring higher transfusion utilization.…”
Section: Discussionsupporting
confidence: 50%
“…Of the 4015 abstracts identified following removal of duplicates, 3924 studies were excluded following title and abstract screening (Figure 1). Of the remaining 91 studies which underwent full‐text review, 21 studies were determined to be eligible and included in the systematic review 8,9,21‐39 . They comprised 7605 anticoagulated hip fracture patients and 13 812 non‐anticoagulated patients (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…13,14 Extensive research has shown that delay to surgery is associated with increased morbidity, mortality, and length of stay in hospital. 15 -19 Despite these findings, patients on DOACs have increased delays to surgery compared to patients on no anticoagulation or on vitamin K antagonists. Average time to surgery for DOAC patients has been shown to vary from 35 hours to 66.9 hours.…”
Section: Introductionmentioning
confidence: 99%
“…Given these uncertainties, it is unsurprising that hip fracture patients taking DOACs experience delays to surgery up to three times longer than non‐anticoagulated patients . Nationally, 6.9% of delays to surgery in the UK are attributable specifically to DOACs; this equates to ~1400 patient delays annually, suggesting that virtually all of the patients receiving DOACs experience delays > 36 h to surgery .…”
mentioning
confidence: 99%